2017
DOI: 10.18203/2394-6040.ijcmph20173818
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards elimination of lymphatic filariasis in two districts of Maharashtra: scenario of last five years

Abstract: Background: Filaria was identified as one of the diseases to be eliminated globally and its global elimination by the year 2020 has been envisaged by World Health Organization (WHO). A large coverage- compliance gap has been found in many MDA programmes in India. Togo is the first sub-Saharan country to have stopped MDAs after prevalence data suggested that LF transmission had been interrupted. The successful Togo program demonstrates that LF elimination can be achieved in countries with limited resources. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Non-consumption or partial consumption of drugs due to many number of pills was expressed as a concern by the respondents which is a universal challenge that may be addressed by strict implementation of supervised consumption. The other reasons for non-receipt/non-consumption of drugs corroborated with findings from other such studies [ 19 23 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Non-consumption or partial consumption of drugs due to many number of pills was expressed as a concern by the respondents which is a universal challenge that may be addressed by strict implementation of supervised consumption. The other reasons for non-receipt/non-consumption of drugs corroborated with findings from other such studies [ 19 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…Available literature reveals that several studies reported coverage estimates (on DA) using different methodologies making it difficult to compare the estimates [ 19 23 ]. The present study is one of the few studies which assessed coverage using the WHO-CSB tool following inclusion of ivermectin in MDA in India [ 19 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[141516] Trend analysis of MDA coverage showed a decline from 80.3% to 77% in the 5 year time interval. [17] Probable reason behind low coverage in present study was that in urban slum setting, dense population with difficult to reach pockets impeded effective communication between providers and beneficiaries. A study from Odisha reported coverage of 48.8% and 77.8% from urban and rural areas, respectively.…”
Section: Discussionmentioning
confidence: 84%